2004
DOI: 10.1038/sj.leu.2403529
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of SHIP activity in a human leukemia cell line downregulates constitutively activated phosphatidylinositol 3-kinase/Akt/GSK-3β signaling and leads to an increased transit time through the G1 phase of the cell cycle

Abstract: The inositol 5-phosphatase SHIP (SHIP-1) is a negative regulator of signal transduction in hematopoietic cells and targeted disruption of SHIP in mice leads to a myeloproliferative disorder. We analyzed the effects of SHIP on the human leukemia cell line Jurkat in which expression of endogenous SHIP protein is not detectable. Restoration of SHIP expression in Jurkat cells with an inducible expression system caused a 69% reduction of phosphatidylinositol 3,4,5-trisphosphate (PtdIns(3,4,5)P 3 ) and a 65% reducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
73
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(75 citation statements)
references
References 63 publications
1
73
1
Order By: Relevance
“…Differential expression of the lipid phosphatase SHIP-1 in CEM and Jurkat cells Previous works have shown that the Jurkat leukemic cell line is deficient in SHIP-1 at the protein level, but that CEM cells express the protein normally (Bruyns et al, 1999;Freeburn et al, 2002;Horn et al, 2004). To confirm that difference in our cell lines, we carried out Western blotting analysis with specific antibodies raised against SHIP-1 and another inositol lipid phosphatase, namely SHIP-2.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…Differential expression of the lipid phosphatase SHIP-1 in CEM and Jurkat cells Previous works have shown that the Jurkat leukemic cell line is deficient in SHIP-1 at the protein level, but that CEM cells express the protein normally (Bruyns et al, 1999;Freeburn et al, 2002;Horn et al, 2004). To confirm that difference in our cell lines, we carried out Western blotting analysis with specific antibodies raised against SHIP-1 and another inositol lipid phosphatase, namely SHIP-2.…”
Section: Resultsmentioning
confidence: 76%
“…Cells lacking SHIP-1 (i.e. Jurkat cells) present a very high basal level of PtdIns(3,4,5)P 3 and a subsequent constitutive Akt activation, which is not the case for SHIP-1-positive cells (Freeburn et al, 2002;Horn et al, 2004). This difference might in turn influence a very large number of cellular events, including IKK activation (Cantley, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…For example, cytolethal distending toxin subunit B (CdtB) is an immunotoxin produced by Actinobacillus actinomycetemcomitans that can hydrolyze PtdIns(3,4,5)P 3 to PtdIns(3,4)P 2 (50). Exposure to CdtB leads to cell cycle arrest and death by apoptosis, consistent with the down-regulation of proliferation observed upon overexpression of SHIP in leukemic cell lines (51). Lymphocytes are considerably more sensitive to CdtB than are other cell types.…”
Section: Lipid Phosphatases Are Exploited By Pathogensmentioning
confidence: 71%
“…7 A SHIP-1 mutant without enzymatic activity was created by exchanging the aspartic acid at position 672 in the second conserved motif of the inositol phosphatase domain to alanine (D672A). The resulting mutant did not reveal any detectable enzymatic activity in an in vitro inositol 5-phosphatase assay using Ins(1,3,4,5)P 4 as substrate (data not shown).…”
Section: Retroviral Vectors and Generation Of Pseudotyped Viral Partimentioning
confidence: 99%
“…Restoration of SHIP-1 activity in a human SHIP-1-deficient leukemia cell line (Jurkat) resulted in a reduced proliferation owing to an increased transit time through the G1 phase of the cell cycle. 7 Juvenile myelomonocytic leukemia (JMML) is a malignant hematopoietic disease of early childhood characterized by excessive proliferation of the myeloid and monocytic lineage. This abnormal myeloproliferation appears to be the result of a selective hypersensitivity of the myeloid JMML progenitor cells to GM-CSF.…”
Section: Introductionmentioning
confidence: 99%